2018
DOI: 10.3390/su10082676
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Social Vulnerability to Flood Disasters in China

Abstract: Abstract:To proactively prevent losses from flood disasters and subsequent potential human conflicts, it is critical to measure the social vulnerability of a country or a region to flood. In this article, we first propose a list of potential indicators for measuring this social vulnerability. These indicators' significances are then tested based on their correlation coefficients with a vulnerability index obtained using nonparametric Data Envelopment Analysis. In the final measurement system, there are nine in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 25 publications
(50 reference statements)
0
8
0
Order By: Relevance
“…The results of this work can be used in future applications as is, or else, researchers could apply the proposed methodology to other natural hazards. [27,35,52,53] Ratio between taxable income and taxpayers in each municipality [39] Fixed investment per inhabitants [71,106] Ratio of investment over the total GDP/revenue-expenditure ratio [47,57] Replacement cost for dwellings located at flood prone area [ Reserve and distribution capacity of flood control materials [45] Emergency rescue capacity of public administration [45] Hospital beds [47,71,100] Medical staff [47,69,71,105] Reception centers [69] Investment in coping capacity [27,64] Preventive measures Land use regulation [60,89] Flood control standards/plans [39,43,94] Hydraulic infrastructures [39] Protective infrastructures Dikes/levees [27,57,66,100] Drainage network/pipelines density [35,43,45,47,52,53,57,68,70,92,94,96] Dams storage capacity/reser...…”
Section: Discussionmentioning
confidence: 99%
“…The results of this work can be used in future applications as is, or else, researchers could apply the proposed methodology to other natural hazards. [27,35,52,53] Ratio between taxable income and taxpayers in each municipality [39] Fixed investment per inhabitants [71,106] Ratio of investment over the total GDP/revenue-expenditure ratio [47,57] Replacement cost for dwellings located at flood prone area [ Reserve and distribution capacity of flood control materials [45] Emergency rescue capacity of public administration [45] Hospital beds [47,71,100] Medical staff [47,69,71,105] Reception centers [69] Investment in coping capacity [27,64] Preventive measures Land use regulation [60,89] Flood control standards/plans [39,43,94] Hydraulic infrastructures [39] Protective infrastructures Dikes/levees [27,57,66,100] Drainage network/pipelines density [35,43,45,47,52,53,57,68,70,92,94,96] Dams storage capacity/reser...…”
Section: Discussionmentioning
confidence: 99%
“…Sharma et al (2018) reviewed the flood disaster research in Nepal and found that Nepalʼs disaster prevention technology needs to be improved. Wang and Zhang (2018) studied disaster‐adapted investments at two ports competing for shippers and found that the probability of large disasters promoted port adaptations, that competition between the ports led to more adaptive investments (“competitive effects”), but that a high degree of change in disaster probability hindered port adaptation. Lam and Kuipers (2019) studied the 2015 Nepalese earthquake recovery and found that the entire reconstruction process had low community involvement and excluded vulnerable groups.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In other recent studies, Shi (2018) studied agricultural flood vulnerability changes in Shanghai suburbs using a CCR DEA model, the results from which provided a scientific decision‐making basis. Zhang et al (2018) used non‐parametric DEA to evaluate China's social vulnerability to floods and found that social vulnerability was primarily affected by the economy, the population, and social security, and to assist governments with disaster risk reduction decisions. The study also took the Yongkang district in Tainan, Taiwan as an example.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Turner et al [29], vulnerability refers to the degree to which a system is likely to experience harm due to exposure to a hazard. Numerous studies have highlighted that the flood vulnerability is multidimensional [4,5,[30][31][32][33] and could be classified into several categories, including physical vulnerability [34][35][36][37], social vulnerability [12,28,36,38,39], economic vulnerability [30,35], and environmental vulnerability [40]. Commonly used vulnerability assessment methods include principal component analysis (PCA), which enables scientists to identify underlying components from a wide range of vulnerability indicators [9,38,41], and multi-criteria analysis method in which several key indicators are selected and weighted to derive a composite vulnerability index [23,42].…”
Section: Introductionmentioning
confidence: 99%